Examples of Neutrosophic Probability in Physics - Fu Yuhua (Neutrosophic Sets and Systems, 2015)
This paper re-discusses the problems of the so-called “law of nonconservation of parity” and “accelerating expansion of the universe”, and presents the examples of determining Neutrosophic Probability of the experiment of Chien-Shiung Wu et al in 1957, and determining Neutrosophic Probability of accelerating expansion of the partial universe.